Dicrostonyx torquatus - Don E. Wilson; Russell A. Mittermeier; Thomas E. Lacher, Jr (Lynx Edicions, 2017)
39. Palearctic Collared Lemming Dicrostonyx torquatus French: Lemming a collier / German: Echter Halsbandlemming / Spanish: Lemming paleértico de collar Other common names: Arctic Lemming, Collared Lemming Taxonomy. Mus torquatus Pallas, 1779, mouth of River Ob, NW Siberia, Russia. Dicrostonyx torquatus 1s in the subgenus Misothermus. In the past, it was treated as a Holarctic species, with five subspecies in Eurasia and 6-12 in North America. Evolutionary split between Palearctic and Nearctic species was first retrieved from chromosomal evidence and cross-breeding experiments and subsequently confirmed by molecular markers and morphometric data. Three subspecies recognized. Subspecies and Distribution. D.t.torquatusPallas,1779—NEEuropeanRussiaandW&CSiberia(WofYeniseiRiver). D.t.chionopaesG.M.Allen,1914—ESiberia(EofYeniseiRiver),includingBolshevikIandNewSiberianIs,EtoChukchiandKamchatkapeninsulas. D. t. ungulatus Baer, 1841 — Novaya Zemlya I (N Russia). Descriptive notes. Head—body 88-140 mm, tail 11-21 mm; weight 63-155 g. Size of the Palearctic Collared Lemming is fairly stable across its entire distribution. It is similar to the Nearctic Collared Lemming (D. groenlandicus) in size, body proportions, color, other peculiarities of external morphology, and craniodental makeup. Its spinalstripe tends to be more distinct and reddish tints more pronounced in the west. Vestigial angles on molars tend to be less well developed than on species in the subgenus Di-Crostonyx. Habitat. Dry and well-drained uplands in high Arctic tundra and forest tundra along southern distributional border. Suitable habitat of the Palearctic Collared Lemming is rich in dicotyledons (avens, Geum, Rosaceae, and dwarf willows, Salix, Salicaceae); cottongrass (Eriophorum) and other sedges (Cyperaceae); grasses (Poaceae); and mosses. Winter habitats are on steep slopes, in depressions, and in peat tundra with thick snow layers. They have been recorded up to elevations of ¢.1400 m in the Ural Mountains and 500-700 m in eastern Siberia. Food ...